Invited Review: The Myosins: Exploration of the Development of Our Current Understanding of These Mutations in the Motor - Moore, Jeffrey R. (2012)
Hypertrophic (HCM) and dilated (DCM) cardiomyopathies are inherited diseases with a high incidence of death due to electrical abnormalities or outflow tract obstruction. In many of the families afflicted with either disease, causative mutations have been identified in various sarcomeric proteins. In this review, we focus on mutations in the cardiac muscle molecular motor, myosin and its associated light chains. Despite the >300 identified mutations there is still no clear understanding of how these mutations within the same myosin molecule can lead to the dramatically different clinical phenotypes associated with HCM and DCM. Localizing mutations within myosin’s molecular structure provides insight into the potential consequence of these perturbations to key functional domains of the motor. Review of biochemical and biophysical data that characterize the functional capacities of these mutant myosins suggests that mutant myosins with enhanced contractility lead to HCM while those displaying reduced contractility lead to DCM. With gain and loss of function potentially being the primary consequence of a specific mutation, how these functional changes trigger the hypertrophic response and lead to the distinct HCM and DCM phenotypes will be the future investigative challenge.